Corpos estranhos? Reflexões sobre a interface entre a intersexualidade e os direitos humanos - Oliveira, Ana Carolina Gondim de Albuquerque (2012)
Between the seventeenth and eighteenth centuries mankind has built as metanarrative belief that truth is the subject of rights in being male or female, causing the human to materialize only in the context of binary sex, disregarding any other form of embodiment. Some people are born with different embodiment of the considered normal, with characteristics of both sexes. They are called the medical discourse of intersex. By transgressing the binary model, these people are relegated to the margins of society, moreover, are relegated to the social invisibility, and repeatedly, raped for their human dignity. This work proposes a reflection on the interface between intersexuality and human rights from the analysis of how the medical and legal knowledge legitimize the sexual binarism and its name, violate the rights and deny personhood to human intersex. The structure of this dissertation is divided into three chapters. In the first chapter an analysis was performed on the construction of bodies as a tool sociocultural- historical concepts such as from the body, gender and sex in the perspective of Michel Foucault, Judith Butler, Bernice Bento, Thomas Laqueur and how legal discourse using these concepts and produces a dogmatist who assumes to know the characteristics of the male from the reflections of Frances Olsen and Carole Pateman. In the second chapter it was analyzed that the medical discourse on intersexuality from the concept, and some type of technical management of intersex bodies and the protocols of surgery grinding sex. Also in the second chapter, was used the prospect of George Canguilhem and Thomas Kuhn to understand the concepts of normality and abnormality are political and cultural rather than biological or natural aimed at discussing the depathologization of intersexuality. In the third and last chapter, it was discussed about how the law legitimizes sexual binarism in scientifically supported biomedical discourse and the practice of surgery that define sex in intersex people hurt human dignity from the analysis of the principles that guide the Universal Declaration on Bioethics and Human Rights. As conclusion it appears that the impotence of the human face of stiff biological destiny transforms human life in a compelling and uncompromising determinism incompatible therefore with the principle of human dignity which justifies the theory of human rights.